Comparison of Oxygen Saturation Dynamics Between Types of Acute Stroke in Early Hospitalization Period - Naura Waliya Maharani; Ita Muharram Sari; Patwa Amani (Biomedical Journal of Indonesia, 2024)
Introduction. Stroke is the number one cause of death and disability in Indonesia. It was found that the incidents of stroke were higher at ages over 45 years. The use of pulse oximeter is an efficient step in monitoring oxygenation in stroke patients. Decreased oxygen levels can cause neurological deficits such as cognitive impairment, causing patients to have problems in attention and executive functions. This study aims to determine the relationship between the type of acute stroke and oxygen saturation in early hospitalization period. Methods. This research was carried out from November to December 2023 at the National Brain Center Hospital, Jakarta, using a cross sectional approach. Information on diagnosis and oxygen saturation values were obtained through medical records, with a total of 70 patients as subjects. Subjects selected through simple random sampling with patients age over 45 years. Statistical analysis used the Mann Whitney test with a significantly different p value <0.05. Results. A total of 68.6% of the subjects were male with ages of 45-59 dominated the subjects at 51.4%. Statistical tests on the type of acute stroke with oxygen saturation values produced a value of p = 0.044 (p < 0.05) on the 3rd day of hospitalization. These results indicate a significant relationship between the type of acute stroke and the oxygen saturation value on the 3rd day of hospitalization. Conclusion. There is a significant correlation between the type of acute stroke and oxygen saturation in the 3rd day of hospitalization.